1994
DOI: 10.1073/pnas.91.22.10265
|View full text |Cite
|
Sign up to set email alerts
|

Specific alteration of the oxidation potential of the electron donor in reaction centers from Rhodobacter sphaeroides.

Abstract: The effects of multiple changes in hydrogen bond interactions between the electron donor, a bacteriochlorophyll dimer, and htdine residues in the reaction center from Rhodobacter sphaeroides have been igaed. Sitedirected mutations were deiged to add or remove hydrogen bonds between the 2-acetyl groups of the dimer and istidine residues at the setry-related sites Hls-L168 and Phe-M197, and between the 9-keto groups and Leu-L131 and Leu-M160. The addition of a hydrogen bond was correlated with an increase in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
342
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(381 citation statements)
references
References 30 publications
39
342
0
Order By: Relevance
“…Such a conclusion has been made on the basis of spectrophotometric measurements of DA related to reversible photooxidation of the primary electron donor, P. As in the case with ferrocyanide (a known exogenous electron donor to P C ), Mn 2C in the presence of bicarbonate accelerated the re-reduction of P C . The midpoint potential for the P C /P of anoxygenic purple bacteria is 0.45-0.50 V (Prince et al 1976;Klimov et al 1977;Lin et al 1994) and a similar E m is found in our work for the pair P C /P in RCs isolated from Rh. iodosum.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Such a conclusion has been made on the basis of spectrophotometric measurements of DA related to reversible photooxidation of the primary electron donor, P. As in the case with ferrocyanide (a known exogenous electron donor to P C ), Mn 2C in the presence of bicarbonate accelerated the re-reduction of P C . The midpoint potential for the P C /P of anoxygenic purple bacteria is 0.45-0.50 V (Prince et al 1976;Klimov et al 1977;Lin et al 1994) and a similar E m is found in our work for the pair P C /P in RCs isolated from Rh. iodosum.…”
Section: Discussionsupporting
confidence: 89%
“…robiginosum and Th. sibirica was found to be equal to 450G30 mV (which is close to E m of P in other purple bacteria; Prince et al 1976;Klimov et al 1977;Lin et al 1994).…”
Section: Resultssupporting
confidence: 53%
“…We assume k in , to a first approximation, to be independent of the mutation. This assumption is supported by the observations of Lin et al (80), who have reported only a weak dependence of the rate of charge recombination between Q A -and P870 + on the reduction potential of P870 + /P870. Any increase of k in with E′ P + /P would if anything lead to an underestimate of K zp .…”
Section: Redox and Kinetic Properties Of Mutationssupporting
confidence: 74%
“…The wild-type RCs were isolated from a deletion strain complemented with the wild-type genes (6). Cells were grown semiaerobically under nonphotosynthetic conditions, and RCs were isolated after published conditions by using lauryl dimethylamine oxide (Fluka) as previously described (7). Crystals were grown with sizes up to 10 mm in length by using conditions similar to those described by Ermler and coworkers (8).…”
Section: Methodsmentioning
confidence: 99%